Kajian Jenis Burung-Burung yang Dipelihara oleh Penghobi dan Tingkat Perdagangannya di Kota Kupang (Studi Kasus di Kecamatan Oebobo dan Kecamatan Kelapa Lima) - Alimus Adrianus Tri Putra; Mari M. E. Purnama; Oki Hidayat; Fadlan Pramatana (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
The phenomenon of bird keeping and trading has become an integral part of community life, especially in urban areas, leading to a dynamic interplay between hobbies, economy, and conservation issues. This qualitative descriptive research aims to examine the types of birds kept by hobbyists and their trade levels, as well as to identify the conservation status of birds found in Oebobo and Kelapa Lima Districts, Kupang City. The study involved 15 informants selected through purposive sampling via observation, interviews, and documentation. The research results show that hobbyists keep 10 bird species: Murai Batu, Kenari, Cucak Ijo, Lovebird, Parkit, Kacer, Perkutut, Tekukur, Finch, and Anis Cendana. The majority of hobbyists (86.67%) have 5-10 years of experience with intensive collections (5-15 birds), dominated by Lovebird, Kenari, and Murai Batu. The primary motivations for hobbyists are personal enjoyment, leisure activities, and business opportunities, supported by active communities. The main problems faced by hobbyists include sick/stressed birds and birds that do not sing (